An amorphous SiAlN barrier coating against NaCl attack in humid air at elevated temperature. (15th July 2022) - Gao, Zhaohe; Kulczyk-Malecka, Justyna; Liu, Han; Kelly, Peter; Xiao, Ping; Chiu, Yu-Lung
Abstract: Amorphous magnetron sputtered SiAlN films have been designed to prevent NaCl attack of Ti alloy substrates in high temperature humid air environments. Uncoated Ti alloys suffer severe degradation after exposure to NaCl deposits in humid air at 700 °C for 100 h, whereas SiAlN coating forms protective scale mainly consisting of sodium silicate in identical conditions. Amorphous sodium silicate exhibits fast Na+ diffusion rate and extremely slow O 2- diffusion rate, but degradation of SiAlN takes place in presence of both O 2- and Na+ species. Sodium silicate scale provides good protection for SiAlN due to slow diffusion of O 2- through sodium silicate. Graphical Abstract: ga1 Highlights: No observable oxide scale formed on the SiAlN coating after oxidation in humid air at 700 °C for 100 h. SiAlN coating forms a protective scale after exposure to NaCl deposits in humid air at 700°C for 100 h. Sodium silicate scale provides good protection for SiAlN due to the slow diffusion of O2- through sodium silicate.